Associations between the Platelet Lymphocyte Ratio and Albumin with Plaque Calcification in Patients with Acute Coronary Syndrome: An Optical Coherence Tomography Study - Kexin Song; Wenjing Yao; Haihao Yan; Yan Zhang; Yanhong Li; Tianxing Li; Qian Yang; Feifei Zhang; Yi Dang (Reviews in Cardiovascular Medicine)
Background: Coronary artery calcification (CAC) is a robust independent predictor of cardiovascular events. Therefore, it is essential to elucidate the factors that influence CAC progression to enhance the outcomes of patients diagnosed with acute coronary syndrome (ACS). This study aimed to investigate the relationship between prevalent laboratory parameters and the calcification of coronary artery plaques in patients diagnosed with ACS by applying optical coherence tomography (OCT). Methods: This single-center, cross-sectional study retrospectively evaluated patients with ACS who underwent percutaneous coronary intervention and OCT examinations at the Hebei General Hospital. Baseline data, laboratory parameters, and OCT imaging were analyzed. Comprehensive statistical analyses were conducted to elucidate the relationship between prevalent laboratory parameters and coronary artery plaque calcification. Results: In this study involving 130 patients, the platelet to lymphocyte ratio (PLR) demonstrated a significant positive correlation with coronary artery plaque calcification (rs = 0.373, p < 0.001), whereas albumin exhibited a significant negative correlation (rs = –0.585, p < 0.001). Both the PLR (odds ratios (OR) 1.011, 95% CI 1.002–1.019, p = 0.014) and albumin levels (OR 0.642, 95% CI 0.539–0.764, p < 0.001) emerged as significant independent predictors of plaque calcification. Receiver operating characteristic curve analysis identified a cutoff point for albumin at <40.65, yielding a sensitivity of 75.8% and a specificity of 77.9%, Comparatively, a PLR >145.04 demonstrated a sensitivity of 61.3% and a specificity of 76.5% for predicting plaque calcification. Conclusions: Albumin and the PLR were significantly associated with plaque calcification in patients with ACS, serving as independent predictors of coronary artery plaque calcification. These parameters may significantly contribute to risk stratification and the future development of preventive strategies to mitigate adverse cardiovascular events.